Internal Temporal Structure of the Biblical Hebrew Verb: A Case Study of Lexical Aspect in the Verb yd’: SBL Annual Meeting 2020 Linguistics and Biblical Hebrew Seminar: Typological and Grammatical Categorization of Biblical Hebrew - Sato, Jun (Journal for Semitics, 2022)
Traditional Biblical Hebrew (BH) grammars have often defined the temporal information of BH verbs only in terms of tense or grammatical aspect, which can be identified by the finite verbal forms. This paper argues that lexical aspect, which is also known as situation aspect or Aktionsart, is an essential semantic factor for determining the internal temporal structure of BH predicates. As a trial cut, this paper analyses lexical aspect in the verb yd' in the qatal, qotel, and wayyiqtol forms.